تلقي الأُمَّة للحديث بالقَبول: النشأة والمفهوم والتطور - عمار أحمد الحريري (International Institute of Islamic Thought, 2016)
يحاول هذا البحث دراسة مصطلح "تلقي الأُمَّة للحديث بالقَبول" في ضوء بُعْدِه الأصولي والحديثي، من حيث النشأة، ومَن استخدمه من العلماء الأوائل، ثم مفهوم هذا المصطلح، والمراد من كلمة: "التلقي"، و"الأُمَّة"، و"القَبول"، وما طرأ على المصطلح من تطور على مستوى المفهوم والتوظيف، ليشتهر في ضوء تلقي الأُمَّة للصحيحين بالقَبول، وليأخذ منحى آخرَ مختلفاً عن نشأته، وذلك تبعاً لدراسة تأصيلية نقدية تتكون من ثلاثة مباحث؛ أولها يتناول نشأة المصطلح وتطوره، وثانيها يركِّز على مفهوم المصطلح وتداخلاته، وثالثها يبحث في تلقي الأُمَّة للصحيحين بالقَبول. This article studies the term "acceptance of the Hadith by the Ummah" in light of its Usuli and Hadith dimensions, considering the emergence of the concept, and the early scholars who used it. The article then deals with the meanings of the terms used in the concept, i.e.: reception, acceptance, and Ummah, and the development and usage of the term in light of the prevailing idea that the Ummah has received the two Sahihs (Bukhari and Muslim) with acceptance, which gave the concept a different meaning than intended. The article applies a critical and Usuli methodology, and is divided into three parts. The first deals with the emergence and development of the concept. The second part concentrates on the concept and its relationships and intervening nature. The third part discusses the idea that the Ummah has received the two Sahihs with acceptance.